Bilateral simultaneous multilayered retinal hemorrhages in a young adult with Idiopathic Thrombocytopenic Purpura (ITP): A rare case report (Nepalese Journal of Ophthalmology, 2020)
Introduction: Idiopathic thrombocytopenic purpura is an autoimmune hematological disorder characterized by isolated low platelet count without any known clinically apparent etiology. Although usually most cases are asymptomatic, it may present with bleeding manifestations in forms of bruises, petechiae, nose bleeding etc. Very rarely, it may present with ocular manifestations in the form of subretinal, preretinal, intraretinal or vitreous haemorrhage.Case: A 26-year-old female presented to the ophthalmology department with chief complaint of sudden painless diminution of vision in both eyes for the last one week. Her best corrected visual acuity for distance was 20/200 in right eye and 20/600 in left eye. Dilated fundus examination showed right eye sub-internal limiting membrane (ILM) haemorrhage, left eye large subretinal and intra-retinal haemorrhages over posterior pole, with Roth’s spot in both eyes. Haematological investigations revealed moderate anaemia (Hemoglobin level of 7 gm %) and severe thrombocytopenia (25,000/ ul). Diagnosis of idiopathic thrombocytopenic purpura (ITP) was made after consultation with an internist. She was treated with systemic steroid and blood transfusion for systemic disease and kept under regular ophthalmic follow up. Over a period of six months, she showed gradual near total resolution of retinal hemorrhages in both eyes and improvement in visual acuity in both eyes.Conclusion: This case gives a unique outlook to simultaneous varied ocular manifestations of ITP in a single patient and stresses upon thorough systemic evaluation in the presence of such manifestations. Optimization of systemic parameters without active ocular intervention in select cases may achieve favourable outcome.